2011
DOI: 10.1186/1746-6148-7-23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 50% and maximal inspired oxygen concentrations on respiratory variables in isoflurane-anesthetized horses

Abstract: BackgroundThe purpose of this study was to compare the effects of 0.5 fraction of inspired oxygen (FiO2) and >0.95 FiO2 on pulmonary gas exchange, shunt fraction and oxygen delivery (DO2) in dorsally recumbent horses during inhalant anesthesia. The use of 0.5 FiO2 has the potential to reduce absorption atelectasis (compared to maximal FiO2) and augment alveolar oxygen (O2) tensions (compared to ambient air) thereby improving gas exchange and DO2. Our hypothesis was that 0.5 FiO2 would reduce ventilation-perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
54
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 33 publications
9
54
3
4
Order By: Relevance
“…In the present study, the delivered volume could not be appropriately reported but it was not allowed to decrease below 10 mL/kg. This is in agreement with previous studies where VT close to 15 mL/kg were maintained with PIP between 22 (Moens et al 1998) and 30 cmH 2 O (Hubbell et al 2011). In humans under general anesthesia, VT as low as 6 mL/kg did not induce more lung atelectasis than traditional VT (Cai et al 2007), but high pressures and large volumes induced more lung injury (Hong et al 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the delivered volume could not be appropriately reported but it was not allowed to decrease below 10 mL/kg. This is in agreement with previous studies where VT close to 15 mL/kg were maintained with PIP between 22 (Moens et al 1998) and 30 cmH 2 O (Hubbell et al 2011). In humans under general anesthesia, VT as low as 6 mL/kg did not induce more lung atelectasis than traditional VT (Cai et al 2007), but high pressures and large volumes induced more lung injury (Hong et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings were reported in a retrospective study comparing 0.8 and 0.6 FIO 2 (Schauvliege et al 2015). Another trial exposing 5 mechanically ventilated horses to 0.5 FIO 2 reported no effect of FIO 2 in mechanically ventilated horses placed in dorsal recumbency (Hubbell et al 2011). In horses anesthetized with isoflurane (Crumley et al 2013) or intravenous anesthetics (Karrasch et al 2015) and breathing spontaneously in dorsal recumbency, the use of 0.5 FIO 2 did not improve the pulmonary gas exchange compared to maximal oxygen concentrations.…”
Section: Discussionsupporting
confidence: 76%
“…Horses anaesthetised with 70 isoflurane in low FiO 2 (0.6) had significantly lower PaO 2 and lower P(A-a)O 2 , but similar 71 PaO 2 :FiO 2 ratios and similar numbers of hypoxaemic animals, when compared to horses 72 anaesthetised with isoflurane in a higher FiO 2 (0.78) (Schauvliege et al, 2015). In two additional 73 studies using oxygen/air mixtures, there was no benefit in using a FiO 2 of 0.5, with no improvement 74 in oxygen delivery and significant hypoxaemia (Hubbell et al, 2011;Crumley et al, 2013). 75…”
mentioning
confidence: 95%
“…Shunt may be due to areas of atelectasis, i.e., blood flow in non-ventilated alveoli. Atelectasis can occur in anesthetized horses due to high fraction of inspired oxygen or simply to animal recumbency (Hubbel and Muir, 2015;Hubbell et al, 2011). When the animal is breathing 100% O 2 , there will only be oxygen in the alveoli, and as it is easily diffused to the blood, the alveoli tends to collapse, causing absorption atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…This was the probable cause of the decrease in PaO 2 in the TG along of anesthesia. Hubbell et al (2011), suggested reducing FiO 2 to 0.5 in order to reduce the occurrence of shunt caused by the absorption atelectasis, however, PaO 2 decreased without a significant improvement in shunt fraction or alveolar dead space ventilation.…”
Section: Discussionmentioning
confidence: 99%